A note on noncosingular lifting modules - Amouzegar, Kalati T.; Keskin, Tütüncü D. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
Let R be a right perfect ring. Let M be a noncosingular lifting module which does not have any relatively projective component. Then M has finite hollow dimension.